THE CHALLENGES OF NURSING PROFESSIONALS IN IMPLEMENTING PALLIATIVE CARE IN HOSPITALIZED PATIENTS (REMUNOM, 2025)
Palliative care emerges as an essential approach to improving the quality of life for patients with advanced chronic illnesses and their families. This care goes beyond conventional medical treatment, addressing physical, emotional, social, and spiritual aspects, and is crucial for alleviating suffering during critical moments. The role of healthcare professionals, especially nurses, is pivotal in this context, requiring specific skills in communication, symptom management, and cultural sensitivity. The formation of a multidisciplinary team is vital to ensuring integrated and personalized care that meets the complex needs of patients. With the increasing prevalence of chronic diseases, the demand for palliative care in adult clinical units has grown, making it imperative to identify these needs early. Clear and empathetic communication between professionals, patients, and families is essential for aligning expectations and facilitating decision-making. Additionally, emotional support plays a crucial role in overcoming the challenges faced in the hospital environment. In summary, the effectiveness of palliative care depends on the competence of professionals, interdisciplinary collaboration, and effective communication. Investing in research and continuous training of healthcare professionals is essential to improve these practices, ensuring increasingly humanized care that meets the needs of patients and their families.